Bronchiectasis and the risk of cardiovascular disease: a population-based study - Navaratnam, Vidya; Millett, Elizabeth R.C.; Hurst, John R.; Thomas, Sara L.; Smeeth, Liam; Hubbard, Richard B.; Brown, Jeremy; Quint, Jennifer K. (BMJ Publishing Group, 2016)
Background: There are limited data on the burden of cardiovascular comorbidities in people with bronchiectasis. Our cross-sectional study estimates the burden of pre-existing diagnoses of coronary heart disease (CHD) and stroke in people with bronchiectasis compared with the general population. The historical cohort study investigates if individuals with bronchiectasis are at increased risk of incident CHD and stroke events.